William Alexander papers - Alexander, William, 1726-1783.
Diary, typewritten transcripts of correspondence, and photostat of orders regarding a patrolling party for the New Jersey coast. Diary (1779) includes the names of the Brigandier, Field Officer, and Brigate Major; a description of courts-martial, command assignments, guard and fatigue details, complaints regarding pay, and similar matters; newspaper clippings (1825-1826); and sketches. Correspondence includes a letter (Philadelphia, Pa.; 1776 January 10) from John Hancock to Alexander, letter (Fishkill, N.Y.; 1778 October 6) from George Washington to Alexander, letter (Philadelphia, Pa.; 1778 November 26) from Henry Laurens to Alexander, and letter (Elizabeth Town, N.J.; 1778 December 1) from Alexander to Laurens concerning the conduct of the war.
In part, typewritten transcripts and photostat.
Continental Army officer. Unsuccessfully claimed earldom of Sterling but was commonly known as Lord Sterling.
Collection material in English.
Keywords: Hancock, John, -- 1737-1793 -- Correspondence; Laurens, Henry, -- 1724-1792 -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; United States. -- Continental Army; United States. -- Continental Army -- Military life; Courts-martial and courts of inquiry; New Jersey -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers